염증성 근육뼈대계 질환에 대한 미세전류의 효과: 메타분석 - 이정우; 고운; 두영택; Lee, Jeongwoo; Ko, Un; Doo, Yeongtaek (Journal of the Korean Society of Integrative Medicine, 2020)
Purpose : The purpose of this meta-analysis was to examine the effects of microcurrent on inflammatory musculoskeletal diseases. Methods : Domestic databases (RISS, NDSL, KISS, DBpia, and Kmbase) were searched for studies that conducted clinical trials associated with microcurrent and its impact on inflammatory musculoskeletal diseases. A total of 606 studies published between 2002 and 2019 were identified, with 8 studies satisfying the inclusion data. The studies were classified according to patient, intervention, comparison, and outcome (PICO). The search outcomes were items associated with blood component, pain, and function. The 8 studies that were included in the study were evaluated using R meta-analysis (version 4.0). The quality of 7 randomized control trials was evaluated using Cochrane risk of bias (ROB). The quality of 1 non-randomized control trial was evaluated using risk of bias assessment tool for non-randomized studies (RoBANS). Effect sizes were computed as the corrected standard mean difference (SMD). A random-effect model was used to analyze the effect size because of the high heterogeneity among the studies. Egger's regression test was carried out to analyze the publishing bias. Results : The following factors had a large effect size involving microcurrent on inflammatory musculoskeletal diseases: blood component (Hedges's g=-2.46, 95 % CI=-4.20~-0.73), pain (Hedges's g=3.51, 95 % CI=2.44~4.77), and function (Hedges's g=3.06, 95 % CI: 1.53~4.58). Except for function (t=1.572, p=.191), Egger's regression test showed that the publishing bias had statistically significant differences. Conclusion : This study provides evidence for the effectiveness of microcurrent on inflammatory musculoskeletal diseases in terms of blood component, pain, and function. However, due to the small sample sizes used in the included studies, the results of our study should be interpreted cautiously, especially considering the publishing bias.